PENGARUH KOMPONEN MASJID AGUNG JAWA TENGAH TERHADAP KEDATANGAN WISATAWAN - Dyah Ayu Paramitha Tunggadewi (Pusat Studi Pariwisata Universitas Gadjah Mada, 2013)
This research is aimed at analyzing the level of strength of the components of Masjid Agung Jawa Tengah in influencing the visit of the tourists coming to the mosque. This research employs “naturalistic” and uses qualitative data analysis. This research explores and links two variables, the components of the mosque and the visit of the tourists. The technique of data collection on the components of the mosque is gained by conducting observation, while for the visit of the tourists it uses the in-depth interview. The data analysis in the components of the mosque is conducted by arranging the data gained in the research from observation, interview, and field note in the narrative text systematically. The data analysis in the the visit of the tourists is conducted by categorizing the data based on the variable from the chosen parameter. The data testing is conducted by using the triangulation technique in the source.The result of the research shows that Masjid Agung Jawa Tengah has strong components in influencing the visit of the tourists. The components of MAJT which become the center of attention for the tourists’ visit are (consecutively) the Asmaul Husna tower, the electric umbrella, the Al Qanatir gate, the function of the building, the mosque’s roof, the minaret in the roof, the mosque’s plaza, the thermal comfort, the audio comfort, the spatial comfort, and also the visual comfort.